The Study Opinions of Thai Tourists Regarding Development of Green Tourism in Natural Tourist Attractions Bangkok - Jaroonsit, Monsira; Pawchit, Chieng (Rajamangala University of Technology Tawan-ok Social Science Journal, 2025)
This research aims to: 1) study Thai tourists’ opinions on natural tourist attractions in Bangkok regarding green tourism, and 2) examine their suggestions for developing these natural attractions into green areas. This qualitative research employed semi-structured interviews as the data collection tool. The key informants consisted of 15 Thai tourists selected through convenience sampling. The interview data were categorized, analyzed by themes, and verified for completeness based on the two research objectives before being summarized as research findings. The results revealed that: 1) Green tourism campaigns remain insufficiently comprehensive across many natural attractions in Bangkok, with some tourists still perceiving limited natural elements. Some respondents believed Bangkok cannot yet be considered a green tourism destination due to the predominance of fuel-powered vehicles and minimal presence of electric or energy-efficient vehicles in the city’s transportation system. 2) All natural tourist attractions in Bangkok should be developed into clean, shady green spaces with environmental conservation measures to establish a positive image as authentic green tourism destinations. This should be coupled with reduced private vehicle use in favor of increased electric train services and expanded green spaces, thereby promoting sustainable tourism industry development.